Analysis of the Consumption of Medicinal Products Associated with a High Risk of Drug-Induced Liver Injury in Patients with COVID-19 - V. I. Petrov; A. Yu. Ryazanova; N. S. Tokareva (Ministry of Health of the Russian Federation, Federal State Budgetary Institution «Scientific Centre for Expert Evaluation of Medicinal Products», 2024)
INTRODUCTION. The risk of liver damage correlates with the severity of COVID-19. However, a growing number of studies have shown an association between liver function impairment and combinations of medicinal products used to treat COVID-19.AIM. The study aimed to analyse the annual consumption of medicinal products associated with a high risk of drug-induced liver injury (DILI) used as part of combination therapy in COVID-19 patients and to review a number of medication administration records in order to develop measures to prevent DILI.MATERIALS AND METHODS. The study used the ATC/DDD methodology to study consumption data for 2020, 2021, and 2022 and analysed a sample of 1250 inpatient medical records and medication administration records of COVID-19 patients treated in a Volgograd region hospital converted into a COVID-19 care centre. For genetically engineered biologicals and cyclophosphamide, which were lacking DDDs, the authors calculated the volume of consumption using the average dose per treatment course. The authors identified medicines capable of causing clinically apparent liver damage (according to the LiverTox database and Russian clinical practice guidelines) and/or elevated liver enzymes in ≥1% of patients (according to safety reports).RESULTS. The study found that 28% of the medicinal products used in combination for inpatient treatment of COVID-19 were associated with a high risk of DILI. In 2020, 2021, and 2022, the total consumption of medicinal products associated with a high risk of DILI was 342.3, 425.3, and 402.3 DDDs per 100 bed days, and the total consumption of genetically engineered biologicals (administered as a single dose) and cyclophosphamide was 3.5, 16.9, and 29.7 average course doses per 100 patients, respectively. According to the selective analysis of medical records, 19.8% (247/1250) reported concomitant use of 5 or more medicinal products associated with a high risk of DILI, which increased the risk of adverse drug interactions leading to DILI. In 2022, the most prescribed medicinal products with a high risk of DILI were omeprazole (188.7 DDDs per 100 bed days), non-steroidal anti-inflammatory drugs and paracetamol (54.4 DDDs per 100 bed days), atorvastatin (46.2 DDDs per 100 bed days), levofloxacin (26.4 DDDs per 100 bed days), ceftriaxone (20.5 DDDs per 100 bed days), favipiravir (17.3 DDDs per 100 bed days), and genetically engineered biologicals (24.0 DDDs per 100 bed days).CONCLUSIONS. To reduce the risk of DILI in COVID-19 patients admitted to infectious disease units, including the risk of DILI due to drug interactions, it is necessary to limit the use of hepatotoxic antibacterial agents, proton-pump inhibitors, and non-steroidal anti-inflammatory drugs, or consider alternative medicinal products with a lower risk of hepatotoxicity.